Studi Literatur : Efektivitas Metode Tanya Jawab dalam Pembelajaran Matematika - Inna Umi Fadillah; Wan Saskia Putri; Julia Agnesia Harianja; Reka Bayu; Christine Amori Damanik; Intan Novita Sari Simanullang (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the effectiveness of the question-and-answer method in mathematics learning. The research method employed is a literature review using a descriptive qualitative approach. Findings from several relevant studies indicate that the question-and-answer method enhances students' learning outcomes, fosters active participation, and strengthens critical thinking and communication skills. Variations in its implementation, such as multi-directional questioning, chain questioning, and experiment-based questioning, enrich classroom interaction and help students grasp abstract mathematical concepts. Furthermore, the method promotes an interactive learning environment where students are encouraged to think critically, reflect on their understanding, and actively engage with their peers. The collaborative nature of the question-and-answer technique supports the development of social skills, making it an effective tool for both cognitive and social learning. Therefore, the question-and-answer method can be considered an effective instructional strategy to improve the quality of mathematics learning, particularly in enhancing problem-solving abilities, fostering a deeper understanding of mathematical concepts, and improving student-teacher interactions.